Molecular simulation of CO2–CH4 competitive adsorption and induced coal swelling - Zhang, J.; Liu, K.; Clennell, M.; Dewhurst, D.; Pervukhina, Marina (2015)
Adsorption isotherms of carbon dioxide (CO2) and methane (CH4) provide crucial information for CO2 sequestration and exploitation of coal seam gas. In this work, we focus on the competitive adsorption behavior of CO2 and CH4 in micropores of an intermediate ranked bituminous coal by performing Monte Carlo (MC) simulations at different injection depths from 300 m up to 3280 m with varying injected gas compositions. An extended poromechanical model enables us to relate our simulation results of adsorption to volumetric strain in the coal. Our simulations show that (i) CO2/CH4 adsorption selectivity, defined as the ratio of the mole fractions of the two species in the adsorbed phase relative to the ratio of the mole fractions in the bulk phase, decreases with increasing injection depth for a fixed injected gas composition, (ii) at a given depth, CO2/CH4 adsorption selectivity decreases as the concentration of CO2 in the injected gas increases, (iii) CO2/CH4 adsorption selectivity appears to be a function of pressure and gas composition at a given temperature. The total adsorption increases with increasing concentration of CO2 in the injected gas at constant gas reservoir pressure. The CO2/CH4 adsorption selectivity decreases with increasing bulk CO2 mole fraction after an initial increase at low pressures, (iv) the volumetric strain has a direct correlation with the injected gas composition and increases with the concentration of CO2 in the injected gas. At 370.2 K the largest volumetric strain of 3.6% is predicted at 30 MPa for pure CO2 adsorption.